Experimental and applied mechanics, volume 6 proceedings of the 2014 Annual Conference on Experimental and Applied Mechanics - Sottos, Nancy R.; Rowlands, Robert; Dannemann, Kathryn (Springer International Publishing, 2015)
Experimental and Applied Mechanics, Volume 6: Proceedings of the 2014 Annual Conference on Experimental and Applied Mechanics, the sixth volume of eight from the Conference, brings together contributions to important areas of research and engineering. The collection presents early findings and case studies on a wide range of topics, including: Advances in Residual Stress Measurement Methods Residual Stress Effects on Material Performance Inverse Problems and Hybrid Techniques Thermoelastic Stress Analysis Infrared Techniques Research in Progress Applications in Experimental Mechanics